Farmers' Perception of the Seriousness of the Declining Groundwater Volume and their Reactions to Mitigation of its undesirable Outcomes (Case Study: The Hamedan - Bahar Plain) - Nemat Hassani; Payam Yadollahi; Ali Asghar Mortazavi (مهندسی منابع آب, 2017)
The declining groundwater resources have jeopardized food security in many marginal drylands. As Iran is dependent on this immensely precious resource that provides some 60% of its needs in hydrologically normal years, and undoubtedly more during droughts, the populace, particularly their irrigation farmers have to be concerned with this dwindling resource. Therefore, the farmers' attitudes towards utilization of groundwater resources are of utmost importance. The purpose of this study, which was implemented through questionnaires, was an assessment of some effective factors, which govern the farmer’s attitudes towards water resources management behaviors in Hamedan-Bahar Plain. Of the 476 farmers who operated wells deeper than 150 meters, 250 were randomly selected for this study. The data were analyzed using the multiple regression analysis based on their answers. The results indicated that understanding of vulnerabilities (β=0.48), realization of the damage (β =0.55), perception of the barriers to water conservation (β =0.57) and acceptance of responsibility for mismanagement of groundwater resources (B=0.42) had significant correlation coefficients (p <0.01).